Recognition of two intracellular cobalamin binding proteins and their identification as methylmalonyl-CoA mutase and methionine synthetase. - Kolhouse, J F (1977)
The granulocyte R-type cobalamin binding protein delivers cobalamin (Cbl) exclusively to hepatocytes, and transcobalamin II delivers Cbl to various mammalian cells. Both protein-Cbl complexes enter cells by pinocytosis, and the protein moieties are rapidly degraded in lysosomes. The liberated Cbl is subsequently bound to a high-molecular-weight intracellular cobalamin binding protein (ICB). The nature of ICB-Cbl is unknown but appears important because ICB-[57Co]Cbl is missing from cultured fibroblasts of a group of patients whose cells take up CN-[57Co]Cbl normally but do not convert it to either of its coenzyme forms. We have examined supernatants of sonicated rabbit livers and have found that 65% of the total endogenous Cbl elutes from Sephadex G-150 as ICB-Cbl and that this fraction also contains the two mammalian Cbl-dependent enzymes, methylmalonyl-CoA mutase (methylmalonyl-CoA CoA-carbonylmutase;EC 5.4.99.2) and methionine synthetase (tetrahydropteroylglutamate methyltransferase; 5-methyltetrahydropteroyl-L-glutamate:L-homocysteine-S-methyltransferase; EC 2.1.1.13). Gradient elution from DEAE-Sephadex reveals that 90--95% of the ICB--Cbl elutes with methylmalonyl-CoA mutase and 5--10% elutes with methionine synthetase. ICB--[57Co]Cbl first appears 2 hr after the intravenous injection of CN[57Co]Cbl bound to granulocyte R-type protein. This ICB-[57Co]Cbl is associated with either methylmalonyl-CoA mutase or methionine synthetase although the latter appears to be formed at a relatively faster rate. Our studies indicate that mammalian cells contain two ICBs, that these proteins are methylmalonyl-CoA mutase and methionine synthetase, and that the primary abnormality in the group of patients mentioned above lies at a step that is common to the formation of both Cbl coenzymes and that precedes the stable binding of Cbl to both methylmalonyl-CoA mutase and methionine synthetase.